Terminating Public Programs: An American Political Paradox - Daniels, Mark R. (Routledge, 1997)
This text examines why and when policies or organizations are terminated, how they can be terminated successfully, and what often prevents them from being terminated. The literature on termination and a variety of case studies are reviewed in order to identify theories supported by research.